Role of Infrastructure to improve quantity and enhance quality of School Education in Sindh Province of Pakistan - Siddique, Mazhar Ali; Tagar, Ali Akbar; Khoso, Zamir Ahmed; Tagar, Hamzo Khan (Advances in Social Sciences Research Journal, 2019)
The study overviews the current status of school’s infrastructure and its nexus with improvement in rate of literacy and improvement in quality of education in the Sindh, the southern province of Pakistan where more than forty percent people are illiterate and females are double than that and these low literacy trends are particularly in far flung area of the region i.e. costal, deserted and hilly region of the rural belt with poor infrastructure and lack of communications at large in compressions of Ruben center’s literacy rate. The paper examines the key infrastructural problems and discuss significance of possibilities in the infrastructural sub sector to improve the structure as a sustainable solution and its impact on literacy trends and quality particularly on female literacy. The study finds that development allocation and utilization trends are increasing but there is no improvement in infrastructure as per utilization’s trends due to mismanagement at large and improper and unsustainable planning on the subject. The major obstacle in the system is the un availability of procurement directorate for well-planned and timely procurement to save the precious available funding with their proper monitoring and best rationalized utilization in decent transparent manners. It is also concluded that significant increase in literacy rate and quality enhancement is strongly correlated with infrastructural improvement at large and should be focused by the policy makers and international donners organizations in the greater interest of human development in the region.